A new perspective of Aristotle’s theory of vision: analysis of the “psycho-physical” intertwined mechanism of vision - Zhao, Qi (Frontiers in Psychology, 2023)
Aristotle’s visual theory plays a pivotal role in De Anima, he specifically analyzes three fundamental elements required for visual activities, namely, color, transparent substance, and light. Color moves and limits transparent substance, thereby transforming transparent substance from potentiality to actuality through light. However, there is a debate between Physicalism and Spiritualism as to the specific implementation of the visual activity. Through the intertwined mechanism, Aristotle’s theory of vision can be clarified. The visual activity is neither purely psychological nor purely physical, it is the “psycho-physical” intertwined mechanism. This is why Aristotle’s visual theory is closely related to contemporary visual psychology.